Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijms21093062
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Mechanisms in Inflammation-Associated Colon Carcinogenesis

Abstract: Patients with chronic inflammatory bowel diseases are at an increased risk of developing colitis-associated cancer (CAC). Chronic inflammation positively correlates with tumorigenesis. Similarly, the cumulative rate of incidence of developing CAC increases with prolonged colon inflammation. Immune signaling pathways, such as nuclear factor (NF)-κB, prostaglandin E2 (PGE2)/cyclooxygenase-2 (COX-2), interleukin (IL)-6/signal transducer and activator of transcription 3 (STAT3), and IL-23/T helper 17 cell (Th17), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 82 publications
1
57
0
2
Order By: Relevance
“…NF-κB as a transcription factor is commonly upregulated in cancer cells and is implicated in the increased synthesis of inflammatory cytokines ( Liu et al, 2020 ). NF-κB not only activates genes associated with cancer cell proliferation, invasion and metastasis, but also induces the expression of inflammatory cytokines and chemokines (e.g., IL-6 and COX-2) ( Hirano et al, 2020 ). NF-κB can crosstalk with STAT3 at multiple levels, and is also a critical target molecule for anti-tumor therapy ( Degoricija et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB as a transcription factor is commonly upregulated in cancer cells and is implicated in the increased synthesis of inflammatory cytokines ( Liu et al, 2020 ). NF-κB not only activates genes associated with cancer cell proliferation, invasion and metastasis, but also induces the expression of inflammatory cytokines and chemokines (e.g., IL-6 and COX-2) ( Hirano et al, 2020 ). NF-κB can crosstalk with STAT3 at multiple levels, and is also a critical target molecule for anti-tumor therapy ( Degoricija et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…35 Among the involved pathways, the aberrant stimulation of NF-κB have been detected in intestinal epithelial cells from both IBD and CRC, 36 and can contribute to inflammation-associated tissue injury 37 as well as tumor cell proliferation via the overexpression of angiogenesis-related genes. 33 In our present study, we have identified a 7-NF-κB-related gene signature (FOS, CCL4, Considering the crucial role in UC and CAC, there is no doubt that the TNF signaling via NF-κB pathway could be highly enriched in CAC samples with significance in our study. The activation of the NF-κB pathway upregulates the expression of pro-inflammatory cytokines and adhesion factors, inhibits the production of apoptotic factors, and promotes tumor angiogenesis and metastasis.…”
mentioning
confidence: 50%
“…The consistent action of inflammatory on intestinal mucosa has been elucidated to predispose UC to CAC by multiple tumor-related genetic changes in intestinal epithelial cells. 32 , 33 Watanabe et al generated 20 discriminator genes to predict the development of CAC among the UC patients, including the cancer-related genes CYP27B1, RUNX3, SAMSN1, EDIL3, NOL3, CXCL9, ITGB2 , and LYN . Nevertheless, they did not distinguish the active UC patients from those in remission.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to mount an appropriate inflammatory response is part of our key defence mechanisms against pathogens and disease; however, it is when inflammation becomes chronic that problems can arise, including acting as a trigger for tumorigenesis [ 105 ]. Chronic inflammation, such as that seen in inflammatory bowel disease (IBD) and ulcerative colitis (UC), is driven by inflammatory mediators such as nuclear factor (NF)-κB and signal transducer and activator of transcription 3 (STAT3), cytokines such as interleukin 6 (IL-6) and prostaglandins, and has been linked to an increased risk of developing cancer [ 106 , 107 , 108 , 109 , 110 ]. Using a model of Rnf20 heterozygous mice to drive depleted H2Bub1, as well as human samples of UC and colorectal cancer, Tarcic and colleagues have shown that loss of H2Bub1 creates a tumour promoting microenvironment in the colon centred on the chronic inflammatory response [ 21 ].…”
Section: Global Loss Of H2bub1 In Human Malignancymentioning
confidence: 99%